Innovative Farm Technologies for small holders of Uttar Pradesh and Uttarakhand - Singh, A K; Dubey, S K; Gautam, U S; Singh, Atar (Indian Farming, 2017)
There are many technological options for diversifying prevalent rice-wheat system in Indo gangetic plains. Of late, diversification through hybrid rice and scented rice, summer mungbean, summer groundnur, goatery, etc. has given lot of windows for the small land holding farmers. The interventions like floriculture, resource conservation practices, water harvesting, polyhouses, plastic mulch, etc. are making farming more sustainable and profitable.